2013
DOI: 10.2105/ajph.2012.301014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Use and Bar Attendance on Smoking and Quit Attempts Among Young Adult Bar Patrons

Abstract: Objectives We examined cigarette smoking and quit attempts in the context of alcohol use and bar attendance among young adult bar patrons with different smoking patterns. Methods We used randomized time location sampling to collect data among adult bar patrons aged 21 to 26 years in San Diego, California (n =1235; response rate = 73%). We used multinomial and multivariate logistic regression models to analyze the association between smoking and quit attempts and both drinking and binge drinking among occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 36 publications
6
64
0
Order By: Relevance
“…More than one-third of the participants aged 18–30 years who completed surveys in the present study were smokers, and research has demonstrated a clear relationship between binge drinking and smoking frequency 24. Evidence suggests that passing clean indoor air acts has been closely related to reduced smoking rates in the USA 10 11.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…More than one-third of the participants aged 18–30 years who completed surveys in the present study were smokers, and research has demonstrated a clear relationship between binge drinking and smoking frequency 24. Evidence suggests that passing clean indoor air acts has been closely related to reduced smoking rates in the USA 10 11.…”
Section: Discussionmentioning
confidence: 54%
“…Evidence suggests that passing clean indoor air acts has been closely related to reduced smoking rates in the USA 10 11. Phantom smokers had lower rates of binge drinking and smoking while drinking at a bar,24 suggesting that smoke-free bars and nightclubs would have the greatest impact on heavier smokers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide important contributions to the existing literature that has shown that these methods can be used to recruit LGBT young adults in bars and nightclubs in a single market [23] and young adults who are at a higher risk for smoking and alcohol use in a number of markets in the United States [24][25][26][27][28].…”
Section: Comparison With Prior Workmentioning
confidence: 84%
“…Researchers are increasingly turning to innovative strategies for recruiting HTR populations versus traditional methods [23][24][25][26][27][28][29][30][31][32][33][34]. One strategy that researchers use to recruit young adults involves conducting intercept interviews in social venues (eg, bars, nightclubs) where the target population spends time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation